The contribution of supply chain technology in Malaysian textile and apparel industry - Lee, Khai-Loon; Hassan, Mohamad Ghozali; Mohamed Udin, Zulkifli (Engineering and Technology Publishing, 2016)
Through the rapid innovation of technology and increasing affordability, it was transformed from a means of convenience to indispensable tools for work, socialization, entertainment, and learning. Given the relevance of the topic, the purpose of this study was aimed to explore the contribution of supply chain technology adoption in Malaysian textile and apparel industry.The nature of this industry is characterized as a huge dynamic flow of physical, information, and financial. Undoubtedly, to handle the delicate nature of this business, the position of supply chain technology has increased not only in the manufacturing sector, but also in smooth movement of upstream and downstream of the supply chain.Thus, the understanding and practicing of supply chain technology adoption has become a crucial prerequisite for keeping competitive in the global race.Even though technology is widely implemented and studied in many industries and countries by researchers, but the study of adoption of supply chain technology in Malaysian textile and apparel industry is insufficient. In view of the significance given to Third Industrial Master Plan by the government Malaysia, it is necessary to recognize the stimulus of supply chain technology adoptions.The results suggest and highlight the extent of supply chain technology adoption and the benefits perceived by textile and apparel companies from supply chain technologies.This study believed that supply chain technology adoption could be beneficial to both internal and external supply chains. The result of this study could be used as a precursor to support future researchers in further investigation on this extent.